(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The research was carried out to investigate the causes of low sanitation and hygiene coverage in Mutare rural ward 15 in Manicaland province, Zimbabwe. The study aimed at establishing factors contributing to low sanitation and hygiene coverage as well as determining the knowledge, attitudes and practices of the community members on sanitation and hygiene. The study was carried out in Mutare rural Ward 15. The community members and programme implementers were selected as study elements. Information was gathered using focus group discussion, interviews and observations. Data collected was presented quantitatively using tables and also qualitatively, providing facts. The stratified and purposive probability sampling was used to draw out household members in the study population. Other subjects in the research included 2 sanitation and hygiene programme implementers, one from Ministry of Health & Child Care and Mutare rural Ward 15 Councilor respectively. The research findings revealed that, low sanitation and hygiene was due to, the community’s negative attitude towards sanitation and hygiene programs, their cultural values, inadequate resources, lack of supervision, as well as the type of soil. This study concluded that knowledge, attitudes and practices of the community, inadequate supervision and resources as well as the type of soil contributed to low sanitation and hygiene coverage. The research therefore recommended that, the community be adequately educated and be provided with enough resources so as to increase coverage in sanitation and hygiene